ANALISIS PENERAPAN ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI IKAN DI PASAR CENDRAWASIH METRO - ahmad fakhri; Eem Desri; Ajeng Intania; Dewi Maharani; Fikri Rizki Utama (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
This study aims to examine how the principles of Islamic business ethics are applied in fish trading activities at Cendrawasih Traditional Market, Metro, Lampung. This study was conducted with a qualitative descriptive approach, using data collection methods through in-depth interviews, direct observation, and documentation with triangulation of data sources and time triangulation. The findings of the study indicate that the implementation of the principles of Islamic business ethics in this market is not yet fully optimal. Some traders still show practices that are contrary to Islamic values, such as not carrying out religious obligations such as prayer, manipulating transactions, and other behaviors that do not reflect the principles of monotheism, justice, and responsibility. On the other hand, there are also traders who have implemented honesty, friendliness, and provided good service to their customers. This shows that there is positive potential that can be developed. Based on the results of the study, more intensive education and coaching efforts are needed to improve the understanding and application of the principles of Islamic business ethics in this traditional market environment, so that trading practices are created that are more in accordance with sharia values.